2014
DOI: 10.4304/tpls.4.1.39-45
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Learning-centered EAP Instruction: An Attempt to Change Students’ Reading Attitude

Abstract: Abstract-There have been remarkable improvements and modifications in TESOL methodology with the advent of post-method era; however, such changes are rarely implemented in fields like ESP. Therefore, a majority of learners and teachers are not satisfied with currently offered EAP courses. Hence, the present study aims at exploring the effect of a Learner-Centered Instruction on undergraduate students' reading attitude in an EAP context. Based on a pedagogical framework driven from Hutchinson and Waters' Learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Recently, it was extended to the English for Academic Purposes domain. Kashef, Pandian, & Khameneh(2014)have implemented the learningcentered approach to change the attitudes and improve the reading skills of 80 undergraduate engineering students.The authors hoped that -a learning-centered EAP instruction which considers the learners' needs and learning process and takes into account the appropriate skills and techniques necessary for this purpose can help the learners accomplish their goals.‖ The study concluded that -a learningcentered instruction which focuses on learners' learning process and needs can change students' negative attitudes toward EAP reading and compensate for their dissatisfaction with teacher-centered EAP classes.‖ The learning-centered approach was also extended to domains far from simple language learning. For example, Li (2015) adapted the learning-centered approach to design a course for students of translation and oral interpreting.…”
Section: Learning-centered Approachmentioning
confidence: 99%
“…Recently, it was extended to the English for Academic Purposes domain. Kashef, Pandian, & Khameneh(2014)have implemented the learningcentered approach to change the attitudes and improve the reading skills of 80 undergraduate engineering students.The authors hoped that -a learning-centered EAP instruction which considers the learners' needs and learning process and takes into account the appropriate skills and techniques necessary for this purpose can help the learners accomplish their goals.‖ The study concluded that -a learningcentered instruction which focuses on learners' learning process and needs can change students' negative attitudes toward EAP reading and compensate for their dissatisfaction with teacher-centered EAP classes.‖ The learning-centered approach was also extended to domains far from simple language learning. For example, Li (2015) adapted the learning-centered approach to design a course for students of translation and oral interpreting.…”
Section: Learning-centered Approachmentioning
confidence: 99%